Influenza A virus hemagglutinin: from classical fusion inhibitors to proteolysis targeting chimera-based strategies in antiviral drug discovery - Francisco Javier Hermoso-Pinilla; Aitor Valdivia; María-José Camarasa; Tiziana Ginex; Francisco Javier Luque (Exploration of Drug Science)
The influenza virus glycoprotein hemagglutinin (HA) participates in critical steps of the attachment of viral particles to the host cell membrane receptor and membrane fusion. Due to its crucial involvement in the initial phases of influenza A infections, HA emerges as a promising target in the search of novel drug-like candidates. Given its pivotal role in the early stages of influenza A infections, intense drug discovery efforts have been undertaken to target HA in the past decades. Drug discovery studies mainly rely on preventing the recognition of sialic acid units by the receptor binding site in the globular head (GH) domain, or the conformational rearrangement required for the fusion of viral and cell membranes. In this work, the aim is to summarize the progress made in HA-targeted development of small molecule fusion inhibitors. To this end, attention will primarily be focused on the analysis of the X-ray crystallographic structures of HA bound to fusion inhibitors. Furthermore, this study also aims to highlight the efforts made in exploiting the structural information in conjunction with molecular modeling techniques to discern the mechanism of action of the fusion inhibitors and to assist the design and interpretation of structure-activity relationships of novel lead compounds will be highlighted. The final section will be dedicated to elucidating novel and promising antiviral strategies proceeding from the transformation of known small molecule antivirals in proteolysis targeting chimera (PROTAC)-based targeted protein degradation. This knowledge will be valuable to assist the exploitation of classical and novel antiviral structure-based strategies, together with a deeper understanding of the mechanism of action and minimization of the impact of drug resistance.